Identification and Isolation of Mollisols in Savadkooh region - N Khakipour; A Akhgar; A Bapiri; A Alipour; AA Miarkolaie (Journal of Applied Sciences and Environmental Management)
The present study was carried out in Savadkooh region, Mazandaran province, North of Iran, to evaluate and identify, what kind of soils are in this area. The study area is under landuse of forest, rice fields and city. The results showed, because of high organic matter and presence of other conditions in forest area, Mollisols were dominant soils in Savadkooh region. Although, we detected 40% Inceptisols, but the similarity of these soils to each other, we guess landuse change, is the main cause to lack of mollic epipedon and decrease in organic matter. So probabely, more than half of Inceptisols, were Mollisols and after changing in landuse, they became Inceptisols. Entisols and Alfisols had the minimun area in Savadkooh. The present study provides a general concept of presentation of Mollisols in Savadkooh region. @JASEM